PENDIDIKAN PESANTREN DAN PERKEMBANGANNYA - Soffan Rizqi; Rifqi Muntaqo; Rahmat Lutfi Guefera (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
Islamic boarding school is a forerunner development of education system in Indonesia. It even has a real contribution to the development of education in Indonesia. Historically, it has extraordinary experience in fostering and developing the society. It is able to increase their roles independently by exploring the potential of the community around them. One of the strategic steps in developing national development goals in the education sector is through enhancing and developing Islamic boarding school. This paper also explains the classification and education model of Islamic boarding school. Therefore, the government also drafts an Islamic boarding school law and religious education which is expected to maximize its potential. The results showed that the Islamic boarding school law and religious education aimed to form individuals who understood and practiced the values ​​of their religious teachings or become religious scholars who believed, have faith, have noble, independent, ta'awun, tawazun, and tawasut. The islamic boarding school law has the advantage of being able to bring into a clearer direction. The drawback is that there is too much intervention in islamic boarding school households. The presence of the Islamic boarding school Law can have both positive and negative effects on the development of Islamic boarding school as a local genius in Indonesia.